PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP HUBUNGAN MANAJEMEN LABA DENGAN NILAI PERUSAHAAN (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2013-2015) - Siti Istiqomah; Hj. Maslichah Hj. Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2017)
The aims of this research : 1) To know the influence of profit management toward the firm value, 2) To know thw influence of Good Corporate Governance toward the firm value, 3) To know the effect of Good Corporate Governance to relationship profit management and companies value. The populationof this research is all of the manufaclture componies that listed in Bursa Efeke Indonesia on 2013-2015. The sampel is selected by using purposive sampling. There were 20 companies that became the sampel of this researt bared on the criteria. This research used double regretive linear design. The result of this research showed that: 1) Profit management was not influence significant toward the firm value, 2) Good Corporate Governance gave negative effect toward the firm value, 3) Good Corporate Governance as the variable moderation was not able to decrease the effect of profit management toward the firm value.